Bone tissue engineering for treating osteonecrosis of the femoral head. Issue 2 (28th February 2023) - Bian, Yixin; Hu, Tingting; Lv, Zehui; Xu, Yiming; Wang, Yingjie; Wang, Han; Zhu, Wei; Feng, Bin; Liang, Ruizheng; Tan, Chaoliang; Weng, Xisheng
Abstract: Osteonecrosis of the femoral head (ONFH) is a devastating and complicated disease with an unclear etiology. Femoral head‐preserving surgeries have been devoted to delaying and hindering the collapse of the femoral head since their introduction in the last century. However, the isolated femoral head‐preserving surgeries cannot prevent the natural progression of ONFH, and the combination of autogenous or allogeneic bone grafting often leads to many undesired complications. To tackle this dilemma, bone tissue engineering has been widely developed to compensate for the deficiencies of these surgeries. During the last decades, great progress has been made in ingenious bone tissue engineering for ONFH treatment. Herein, we comprehensively summarize the state‐of‐the‐art progress made in bone tissue engineering for ONFH treatment. The definition, classification, etiology, diagnosis, and current treatments of ONFH are first described. Then, the recent progress in the development of various bone‐repairing biomaterials, including bioceramics, natural polymers, synthetic polymers, and metals, for treating ONFH is presented. Thereafter, regenerative therapies for ONFH treatment are also discussed. Finally, we give some personal insights on the current challenges of these therapeutic strategies in the clinic and the future development of bone tissue engineering for ONFH treatment. Abstract : Great progress has been made in ingenious bone tissue engineering for osteonecrosis of the femoral head (ONFH) treatment in the last decades. In this review, we comprehensively summarize the state‐of‐the‐art progress made in bone tissue engineering for ONFH treatment. We also propose insights on the current challenges of these advances in the clinic and the future development of bone tissue engineering for ONFH treatment.